Studying the relationship between transformational leadership, organizational learning, organizational innovation, and organizational performance - an empirical study in Vietnamese small and medium enterprises - Dang, Ha Thu; Tran, Nu the; Truong, Hang Thanh (Edelweiss Applied Science and Technology, 2025)
This study examines how transformational leadership, organizational learning, and organizational innovation influence organizational performance in small and medium-sized enterprises (SMEs) in Vietnam. A quantitative research design was employed, using survey data collected from 283 managers of SMEs across various industries between October 2023 and July 2024. Structural equation modeling was applied to test the proposed relationships among the variables. The results indicate that transformational leadership, organizational learning, and organizational innovation all exert direct and significant positive effects on organizational performance. Among these factors, organizational innovation demonstrates the strongest impact, followed by transformational leadership and organizational learning. In addition, organizational learning and organizational innovation serve as mediators in the relationship between transformational leadership and organizational performance. The study highlights the critical role of leadership, learning, and innovation in improving business outcomes within dynamic and competitive environments. The findings provide valuable insights for enterprise leaders and policymakers seeking to strengthen organizational effectiveness through capability development, knowledge-sharing practices, and innovation-driven strategies.